2014
DOI: 10.1002/cncr.28561
|View full text |Cite
|
Sign up to set email alerts
|

A phase 2 trial of dacomitinib (PF‐00299804), an oral, irreversible pan‐HER (human epidermal growth factor receptor) inhibitor, in patients with advanced non–small cell lung cancer after failure of prior chemotherapy and erlotinib

Abstract: BACKGROUNDThis phase 2 trial (ClinicalTrials.gov identifier NCT00548093) assessed the efficacy, safety, and impact on health‐related quality of life of dacomitinib (PF‐00299804), an irreversible tyrosine kinase inhibitor (TKI) of human epidermal growth factor receptors (EGFR)/HER1, HER2, and HER4, in patients with KRAS wild‐type non–small cell lung cancer (NSCLC).METHODSPatients with advanced NSCLC, progression on 1 or 2 regimens of chemotherapy and erlotinib, KRAS wild‐type or known EGFR‐sensitizing mutant tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 125 publications
(89 citation statements)
references
References 22 publications
2
87
0
Order By: Relevance
“…Dacomitinib has shown significant therapeutic efficacy in NSCLC, specifically to tumours that have not previously responded to conventional single receptor inhibitors, and also against tumours with mutations developed for acquired resistance of targeted therapies [37][38][39]. Dacomitinib is currently in phase III clinical trials, and the most commonly reported adverse event among all trials has been diarrhoea, commonly resulting in dose reductions and patient withdrawal from clinical trials [38,39,[42][43][44] (Table 3).…”
Section: Second-generation Human Epidermal Growth Factor Receptor Tyrmentioning
confidence: 99%
“…Dacomitinib has shown significant therapeutic efficacy in NSCLC, specifically to tumours that have not previously responded to conventional single receptor inhibitors, and also against tumours with mutations developed for acquired resistance of targeted therapies [37][38][39]. Dacomitinib is currently in phase III clinical trials, and the most commonly reported adverse event among all trials has been diarrhoea, commonly resulting in dose reductions and patient withdrawal from clinical trials [38,39,[42][43][44] (Table 3).…”
Section: Second-generation Human Epidermal Growth Factor Receptor Tyrmentioning
confidence: 99%
“…39,61,62 Acquired PIK3CA mutations have been described in 5% of relapsed lung ACAs, 31 but are also seen in concert with EGFR (and other driver gene) mutations in untreated samples. 63 The mechanisms underpinning a morphologic transformation to small cell carcinoma are unknown.…”
Section: Mechanisms Of Resistance To Egfr Inhibitorsmentioning
confidence: 99%
“…Second generation EGFR TKIs, such as afatinib and dacomitinib, failed to overcome significant acquired resistance to erlotinib and gefitinib [7]. CO1686 and AZD9291 are third generation EGFR TKI which can irreversibly bind to EGFR sensitising mutations, as well as the acquired T790M mutation, with high selectivity as compared to wild-type EGFR [8].…”
Section: -Year Long-term Survival Of a Metastatic Egfr-mutated Nonsmentioning
confidence: 99%